Determination of Death by Neurologic Criteria in the United States: The Case for Revising the Uniform Determination of Death Act. (December 2019) - Lewis, Ariane; Bonnie, Richard J.; Pope, Thaddeus; Epstein, Leon G.; Greer, David M.; Kirschen, Matthew P.; Rubin, Michael; Russell, James A.
Although death by neurologic criteria (brain death) is legally recognized throughout the United States, state laws and clinical practice vary concerning three key issues: (1) the medical standards used to determine death by neurologic criteria, (2) management of family objections before determination of death by neurologic criteria, and (3) management of religious objections to declaration of death by neurologic criteria. The American Academy of Neurology and other medical stakeholder organizations involved in the determination of death by neurologic criteria have undertaken concerted action to address variation in clinical practice in order to ensure the integrity of brain death determination. To complement this effort, state policymakers must revise legislation on the use of neurologic criteria to declare death. We review the legal history and current laws regarding neurologic criteria to declare death and offer proposed revisions to the Uniform Determination of Death Act (UDDA) and the rationale for these recommendations.